Antibodies against peptides of NMDA-type GluR in cerebrospinal fluid of patients with epileptic spasms. (November 2016) - Mori, Tatsuo; Takahashi, Yukitoshi; Araya, Nami; Oboshi, Taikan; Watanabe, Hirokazu; Tsukamoto, Kazuki; Yamaguchi, Tokito; Yoshitomi, Shinsaku; Nasu, Hirosato; Ikeda, Hiroko; Otani, Hideyuki; Imai, Katsumi; et al.
Abstract: Objective: We investigated the contribution of antibodies against N-methyl-d -aspartate (NMDA)-type glutamate receptor (GluR) in cerebrospinal fluid (CSF) to the clinical features of patients with epileptic spasms (ES). Methods: CSF samples were collected from 33 patients with ES with median (range) age 1.8 (0.2–8.5) years. Thirty patients without ES with 3.5 (0.5–7.0) years were also studied as disease controls. The CSF levels of antibodies against peptides of NMDA-type GluR subunits (GluN2B & GluN1) were measured by enzyme-linked immunosorbent assay. Results: The levels of antibodies against the n-terminal of GluN2B (GluN2B-NT2), c-terminal of GluN2B (GluN2B-CT) and n-terminal of GluN1 (GluN1-NT), were significantly higher in patients with ES than in disease controls (p < 0.01, p < 0.01 & p = 0.03). Levels of antibodies to GluN2B-NT2 & CT were not related with ACTH therapy nor conventional CSF factors (cell counts, protein level, etc). Levels of antibodies to GluN2B-NT2 & CT showed evidence of correlation within a linear regression model with intervals from the onset to the examination of CSF until 25 months (p = 0.01 & p = 0.01). The correlation was significant in patients with unknown cause (p = 0.01). Five of 33 patients (four unknown cause & one chromosomal anomaly) had higher level of antibodies to GluN2B-NT2 exceeding mean + 1 SD of all ES patients, and they had poor motor (score 0) and cognitive outcomes (score 0 or 1). Conclusion: The CSF level of antibodies against GluN2B in ES patients with unknown cause was estimated to increase after onset. We hypothesize that some ES patients may have immune process after the onset of ES. Highlights: The role of antibodies to NMDA-type GluR in CSF was investigated in ES patients. Significant difference of the antibodies between ES and disease controls was shown. Predictive value of antibodies for outcome was not confirmed. GluN2B antibodies were higher especially in ES patients with unknown cause. We suggested possible contribution of GluN2B antibodies to motor and cognitive outcomes.